From Implicit and Explicit Reason to Inference and Assent: The Significance of John Henry Newman’s Seminary Studies in Rome - Shea, C. Michael (The journal of theological studies, 2016)
The present article focuses on the significance of John Henry Newman’s Roman seminary studies in 1846-7 for the development of his reflections on faith. As an Anglican, Newman envisaged faith from the conceptual binary of ‘implicit’ and ‘explicit reason’. After encountering scholastic categories on the question as a Roman Catholic neophyte, Newman came to regard his earlier approach as insufficient in accounting for the various features of faith, such as the notion of human free will. In Rome, the Jesuit professor of dogmatic theology Giovanni Perrone helped Newman to revise his earlier position. Perrone’s standard theological textbook, the Praelectiones Theologicae , defined faith as a specific type of intellectual assent. Newman regarded Perrone and his textbook as authoritatively expressing Roman Catholic orthodoxy on the question of faith, and it is during this period that one encounters Newman’s first full-scale reconsideration of his earlier views and first explicit definition of faith as an intellectual assent. Consequently, Newman’s later contributions to the problem of faith, including his magnum opus An Essay in Aid of a Grammar of Assent (1870), owe a significant debt to this watershed period in his life.